Knowledge and Awareness of Emotional Artificial Intelligence as Tool in Child's Oral Health Care Assessed Among Dental Professionals of Eastern India. A Cross Sectional Study - Varsha Sharma; Mukul Sharma; Brahmananda Dutta; Anandamoy Bagchi (Wolters Kluwer Medknow Publications, 2024)
Background: One of the most crucial steps in providing the child's oral health care and treatment needs is modifying his/her behavior, mood and emotion in any primary care/dental home or any speciality centre. This is very important parameters for any dental professionals and paediatric dentist. Through this study we investigated the knowledge, awareness of Emotional Artificial Intelligence (AI) as tool for modifying their behaviour prior to any treatment requirement. Materials and Methods: The study was conducted among dental professionals of located in different regions of eastern India. We used a consecutive sampling method to collect our sample. Results: Out of the 120 participating dental professionals, 30% professionals believed that emotional AI could monitor a child's acceptance to treatment. Despite a low perception level of emotional AI by the dentist, 71% agreed on the beneficial effect of Emotional Artificial Intelligence (AI) in an emergency or uncooperative child if such technology exist. Conclusion: Regression model showed that certain key influencers can increase the quality of healthcare by 3 times which could favors Emotional Artificial Intelligence as an adjunct to Pediatric dentists in managing children.